2015
DOI: 10.1038/npp.2015.314
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for Thalamocortical Circuit Abnormalities and Associated Cognitive Dysfunctions in Underweight Individuals with Anorexia Nervosa

Abstract: Anorexia nervosa (AN) is characterized by extremely low body weight resulting from pathological food restriction, and carries a mortality rate among the highest of any psychiatric illness. AN, particularly during the acute, underweight state of the illness, has been associated with abnormalities across a range of brain regions, including the frontal cortex and basal ganglia. Few studies of AN have investigated the thalamus, a key mediator of information flow through frontal-basal ganglia circuit loops. We exam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
43
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(49 citation statements)
references
References 56 publications
4
43
0
2
Order By: Relevance
“…AN and BN patients show reduced gray matter volume specifically in SN regions including the caudate nucleus, anterior cingulate cortex and insula, among other areas (Schäfer et al, 2010; Friederich et al, 2012; Frank et al, 2013; Coutinho et al, 2015). On DTI, AN patients show abnormal thalamic connectivity to the dlPFC and anterior PFC (Frieling et al, 2012; Hayes et al, 2015), and reduced fractional anisotrophy in the medial dorsal thalamic radiations (Biezonski et al, 2015; Hayes et al, 2015). Further, increased structural connectivity between the insula and striatum is observed in ED (Frank et al, 2016; Shott et al, 2016).…”
Section: Abnormalities Of Sn-cstc Loop Circuits In Psychiatric Illnessesmentioning
confidence: 99%
“…AN and BN patients show reduced gray matter volume specifically in SN regions including the caudate nucleus, anterior cingulate cortex and insula, among other areas (Schäfer et al, 2010; Friederich et al, 2012; Frank et al, 2013; Coutinho et al, 2015). On DTI, AN patients show abnormal thalamic connectivity to the dlPFC and anterior PFC (Frieling et al, 2012; Hayes et al, 2015), and reduced fractional anisotrophy in the medial dorsal thalamic radiations (Biezonski et al, 2015; Hayes et al, 2015). Further, increased structural connectivity between the insula and striatum is observed in ED (Frank et al, 2016; Shott et al, 2016).…”
Section: Abnormalities Of Sn-cstc Loop Circuits In Psychiatric Illnessesmentioning
confidence: 99%
“…It is used to investigate the functional architecture of the brain at rest (Lee, Smyser, & Shimony, ). In AN, a number of rs‐fcMRI studies have demonstrated evidence of disturbed functional connectivity in brain regions associated with cortico‐striato‐thalamo‐cortical (CSTC) circuitry which have also been implicated in OCD (Biezonski, Cha, Steinglass, & Posner, ; Cha et al, ; Ehrlich et al, ; Haynos et al, ). Using network‐based statistics (NBS), Ehrlich et al identified reduced functional connectivity in a thalamo‐insular subnetwork among underweight adolescents and young adults with AN relative to healthy control participants (HC) (Ehrlich et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Using network‐based statistics (NBS), Ehrlich et al identified reduced functional connectivity in a thalamo‐insular subnetwork among underweight adolescents and young adults with AN relative to healthy control participants (HC) (Ehrlich et al, ). Another study measuring thalamo‐frontal functional connectivity in acutely ill individuals with AN relative to HC found evidence of altered connectivity between the thalamus and both the dorsal and anterior prefrontal cortices which were associated with impairments in tasks measuring cognitive control and working memory, respectively (Biezonski et al, ). Haynos et al () used a seed‐based approach to investigate ventral and dorsal frontostriatal circuits and found evidence of reduced functional connectivity in both circuits among underweight individuals with restricting type AN relative to HC.…”
Section: Introductionmentioning
confidence: 99%
“…The IFG is part of the cognitive control system of the brain which governs response inhibition (27). Furthermore, alterations in connectivity between the thalamus and the prefrontal cortex have also been seen in AN, which may play a role in the cognitive dysfunction seen in this group (28). In a study using whole-brain ICA to examine RSNs in a population of adolescents with AN, decreased functional connectivity between the executive network and the anterior cingulate was reported, which might contribute to impaired cognitive flexibility in relation to the control of appetite and body image in AN (29).…”
Section: Introductionmentioning
confidence: 99%